Politically motivated trade protection - Chad P. Bown; Paola Conconi; Aksel Erbahar; Lorenzo Trimarchi (Asian Development Bank (ADB), 2024)
This paper shows that the Electoral College system used to elect presidents of the United States (US) distorts US federal policies in favor of key industries in swing states. Using detailed data on US trade policies during the past few decades, we find that the level of trade protection granted to an industry during a presidential term depends on its importance in expected swing states in elections at the end of that term. Crucially, swing-state politics only matters during first terms, when the incumbent president can be reelected. We next examine the effects of politically motivated trade protection, exploiting exogenous changes in the identity of swing states across terms and heterogeneous exposure to these political shocks across industries. We find that swing-state politics generates winners and losers: it fosters growth in protected industries, but hampers growth in downstream industries.
Keywords: D72; D78; F13; 330; Electoral College; swing states; trade protection; supply chains